2014
DOI: 10.1055/s-0038-1671999
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anti-Bacterial and Anti-Inflammatory Properties of Neem, Curcumin and Aloe Vera in Conjunction with Chlorhexidine as an Intracanal Medicament – an In-Vivo Study.

Abstract: Aim & Objective: The main aim of this study was to evaluate the potential of Neem, Curcumin and Aloe vera as an effective intracanal medicament in root canal therapy of infected teeth and to determine the antimicrobial and anti-inflammatory properties of these three herbal substances used in the study. Material and Method: In this study, thirty three patients(33) within the age group of 25-40 years with two single rooted anterior teeth, presenting with periapical radiolucency requiring endodontic therapy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Curcumin's antibacterial effect as an intracanal medicament on planktonic bacteria has been shown to be significantly lower than chlorhexidine[ 28 32 ] but superior to A. vera and calcium hydroxide,[ 32 ] while in the present study conducted on biofilm state, the antibacterial activity of curcumin was equal to calcium hydroxide and superior to A. vera .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Curcumin's antibacterial effect as an intracanal medicament on planktonic bacteria has been shown to be significantly lower than chlorhexidine[ 28 32 ] but superior to A. vera and calcium hydroxide,[ 32 ] while in the present study conducted on biofilm state, the antibacterial activity of curcumin was equal to calcium hydroxide and superior to A. vera .…”
Section: Discussionmentioning
confidence: 54%
“…[ 27 ] Due to some side effects and increased microbial resistance to calcium hydroxide, research on herbal drugs with less toxicity and fewer expenses is flourishing. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Khetarpal et al . (2014) stated that the presence of nimbidin and nimbolide, which are the active constituents of Neem can cause bacterial cell wall lysis. Neem also plays a role as an anti‐inflammatory agent by regulating the pro‐inflammatory enzymes such as cyclooxygenase (COX) and lipoxygenase (LOX) (Alzohairy 2016).…”
Section: Discussionmentioning
confidence: 99%
“…32 Khetarpal et al reported that Curcuma longa showed pre-operative mean colony count of 12.55 and post operative mean colony count was 5.00 that is significant reduction of bacteria. 20 In Group II -Median colony count (CFU/ml) in Preoperative & Post-operative samples were 452 (CFU/ml) and 207 (CFU/ml) respectively. There was statistically significant reduction in the colony counts from Preoperative to Post-operative samples (P<0.01).…”
Section: Discussionmentioning
confidence: 94%
“…The antibacterial efficacy of both curcumin and aloe vera, though researched, require further studies to support their effective use as an intracanal medicaments. 20,21 Under in vivo conditions, mixed endodontic infections may show a different sensitivity or reaction towards the disinfecting agent. In vivo antibacterial studies, which combine physiological and bacteriological dynamics, have a greater clinical relevance than in vitro tests.…”
Section: Discussionmentioning
confidence: 99%